Reducing Ethnocentrism through Multiculturalism and Social Learning in Multicultural Societies - Tagle, Arturo (Future Science / FSH-PH Publications, 2021)
Ethnocentrism is the belief that one’s own culture is centrally important and is superior to other cultures, and influences how people would communicate with others from different cultural backgrounds in a multicultural society. This study describes the perceptions of criminology faculty and students towards reducing ethnocentrism through multiculturalism and social learning. This quantitative descriptive research determined the perceptions of 50 purposively selected faculty member and 125 criminology students from selected universities in Metro Manila towards reducing ethnocentrism through multiculturalism and social learning. The researcher-developed questionnaire was administered online using Google Form. Data privacy and confidentiality were considered during the conduct of the entire study. Data were analysed using frequency and percentage distribution, mean, and rank. The majority of the respondents belong to the age group of 20 and younger. The respondents were dominated by males, and were singles. The majority of student respondents were in the first year. The majority of faculty respondents have master’s degree and 1- 10 years of teaching experience, and were regular/permanent employees. In terms of monthly gross income, 25 or 50% of faculty respondents earn P 30,000- 39,999.00. The majority of the faculty and criminology students believed that ethnocentrism can be reduced through multiculturalism and social learning, such that, social learning can be activated through self-awareness to tolerating differences to appreciating the benefits of differences. As gleaned from the study, ethnocentrism can be reduced by modeling an open-minded and accepting organizational climate amidst cultural diversity and complimenting social learning in developing social intelligence, promoting mutual respect, and active listening that leads to intercultural collaboration in this culturally diverse police force and societies.